How to win real-life Monopoly: the roles of tax havens and finance in the monopolisation of multinational corporations - Nadarajah, Kristin Dilani (My University, 2022)
Much like individual income inequality, there is an increasing gap between top corporations and the rest, in terms of revenue, profits, and power more broadly. This gap is reinforced and exacerbated by the largest corporations’ ability to minimise taxes through the use of tax havens and the offshore system. There has been extensive research mapping the issue of corporate tax avoidance, as well as documenting the rise of market and monopoly power (concentration), however, there is less research combining these two. Monopoly power is thoroughly dealt with in the Monthly Review School tradition with their monopoly capital roots. Recent developments within the tradition have also incorporated finance as a key aspect of the tendency of capital to concentrate and centralise. Nevertheless, tax havens and the system around them have been excluded from this debate. This paper finds that tax havens play a crucial role in the process of concentration and centralisation of capital for three key reasons: (i) they act as a driver of financialisation which in turn accelerates the centralisation process, (ii) they provide cost minimising tools which have become central parts of capital accumulation, and (iii) they contribute to creating more opaque markets and increase the competitive advantages of the giant corporations, allowing them to increase barriers to entry. Tax havens and their usage by multinational corporations (MNCs) must therefore be seen as a systematic issue that plays a key role in not only the financial system, but also in the economy and capitalist system as a vehicle of capital accumulation in the hands of a few.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: Revenue; Income inequality; Multinational corporations